Principal Management in Increasing the Quality of Education in the Society 5.0 Era - Khairunnisa Putri Alif; Salma Nabila; Masduki Ahmad (Indonesian Journal Of Educational Research and Review, 2022)
The industrial revolution is a concept that facilitates human life with AI as its main component. Even though society 5.0 uses modern technology, the quantity of several AI applications still needs to be bigger and being produced and developed further. This circumstance sparked new developments. Education must be able to adapt to these changes appropriately. This research aims to analyse the management of school principals in improving the quality of education in the era of society 5.0. This study uses a qualitative approach by collecting data from previous research and then looking at the results of interviews, observations, and documentation by respondents, namely the school principal. The method used in this research is a literature review of books, scientific articles, and literature sources of books, scientific articles, and other literary sources. The literature study results explain that the management of school principals in the era of society 5.0 is required to keep up with digital developments because it dramatically affects the quality of education. In improving the quality of education in society 5.0, one of the most critical factors in achieving this is ensuring that school leaders are empowered in educational institutions where they can carry out effective and efficient leadership.